2014
DOI: 10.1371/journal.ppat.1004200
|View full text |Cite|
|
Sign up to set email alerts
|

Ubiquitin-Mediated Response to Microsporidia and Virus Infection in C. elegans

Abstract: Microsporidia comprise a phylum of over 1400 species of obligate intracellular pathogens that can infect almost all animals, but little is known about the host response to these parasites. Here we use the whole-animal host C. elegans to show an in vivo role for ubiquitin-mediated response to the microsporidian species Nematocida parisii, as well to the Orsay virus, another natural intracellular pathogen of C. elegans. We analyze gene expression of C. elegans in response to N. parisii, and find that it is simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
405
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(415 citation statements)
references
References 99 publications
(130 reference statements)
9
405
1
Order By: Relevance
“…Knock-down of lgg-1 and atg-18 (encoding the homolog of human WIPI1) by RNAi resulted in increased bacterial load, indicating that autophagy is required for controlling N. parisii infection. In addition, examination of transgenic worms carrying a translational GFP reporter for LGG-1 revealed that the autophagy machinery is targeted to N. parisii cells [42]. (iii) Infection with the extracellular pathogen S. aureus also activates the expression of several autophagy genes and this activation is dependent on the bHLH transcription factor HLH-30, which is required for the expression of 80% of the transcriptional C. elegans response to S. aureus, including AMP genes [23].…”
Section: (B) Autophagymentioning
confidence: 99%
“…Knock-down of lgg-1 and atg-18 (encoding the homolog of human WIPI1) by RNAi resulted in increased bacterial load, indicating that autophagy is required for controlling N. parisii infection. In addition, examination of transgenic worms carrying a translational GFP reporter for LGG-1 revealed that the autophagy machinery is targeted to N. parisii cells [42]. (iii) Infection with the extracellular pathogen S. aureus also activates the expression of several autophagy genes and this activation is dependent on the bHLH transcription factor HLH-30, which is required for the expression of 80% of the transcriptional C. elegans response to S. aureus, including AMP genes [23].…”
Section: (B) Autophagymentioning
confidence: 99%
“…These observations suggest that DRH-1 might function as a sensor of viral RNA, analogous to RIG-I, but instead trigger an RNAi response (26). Others have argued that [17,28,43]). Virus infection and replication leads to the production of viral dsRNA that triggers the antiviral RNAi pathway.…”
Section: Nonnatural Virus Models (I) Flock House Virusmentioning
confidence: 99%
“…These fungal-related pathogens have been recovered from wild-caught nematodes, and one species, Nematocida parisii, causes a lethal intestinal infection in C. elegans (12). Examination of transcriptional responses to N. parisii infection identified a set of differentially regulated genes (DEGs) that shared a large degree of overlap with DEGs found after OV infection but little overlap with DEGs observed after infections with extracellular pathogens (43,44). This suggested that there might be a unique host response to intracellular pathogens.…”
Section: Nonnatural Virus Models (I) Flock House Virusmentioning
confidence: 99%
See 2 more Smart Citations